Evaluation of Tissue Repair Using MRI Imaging of Human Intervertebral Discs Cultured in a Bioreactor. Issue 1 (April 2016) - Rosenzweig, Derek H.; Gawri, Rahul; Moir, Janet; Beckman, Lorne; Eglin, David; Steffen, Thomas; Roughley, Peter; Ouellet, Jean; Haglund, Lisbet
Introduction: Low back pain is a major problem world-wide, affecting the quality of life for millions of people. Low back pain also has a tremendous impact on direct and indirect global healthcare costs. Intervertebral disc (IVD) degeneration has been strongly associated with low back pain. Long-term organ culture of human IVDs is essential to study IVD degeneration and repair. Using an ex vivo approach, the relationship between mechanobiology, disc matrix composition and metabolism can be better understood in the context of degenerative disease. We have developed a bioreactor where intact human discs can be cultured in a controlled dynamically loaded environment. Here, we aimed to determine the most suitable loading parameters for human discs culture by assessing IVD tissue integrity and cell viability under low, medium and high magnitude cyclic load. Furthermore, we investigated the suitability of this model toward cell supplementation strategies for tissue repair and developed a novel, single disc MRI imaging sequence aimed at direct visualization of tissue repair. Materials and Methods: Human IVDs were isolated from lumbar spine segments as previously described. Spines were obtained with consent through the Transplant Quebec Organ Donation Program from individuals who had undergone sustained brain death. Discs were cultured under 3 different loading schemes to mimic a sedentary lifestyle: low 0.1–0.3, medium 0.1–0.6 and high 0.1–1.2 MPa loads. Cell viability and matrix stability was assessed following 10 days of loading. Feasibility of cell/hydrogel implantation was determined over 14 days of medium dynamic loading. To determine whether isolated discs could be imaged by MRI, extracted individual discs were visualized for T1 and T2 signals using a novel sequence using a small animal Bruker 7.5 Tesla MRI. Results: Cell viability was maintained at greater than 80% throughout the discs at low and medium loads. Viability dropped to ~60–70% throughout the discs under high loads. Proteoglycan content remained stable in all loading protocols (~50 μg sGAG/mg tissue), as did CHAD and newly synthesized collagen II protein. To test for feasibility of cell therapies in the bioreactors, NP cells combined with a hydrogel were injected into discs and cultured under medium load. 14 days after dynamic culture, the injected cells were mainly localized to the NP region with greater than 90% viability. The small animal MRI was able to obtain well-defined images of isolated discs, with details of tissue integrity and proteoglycan content. Conclusion: Our ex vivo model of dynamic human IVD culture can be used as a platform on which to study mechanisms of degeneration as well as for novel avenues aimed at biological repair using bioactive substances or cell based therapies. Cells and bioactive substances can be administered within hydrogels thereby enhancing the reparative properties. Furthermore, it is feasible to assess repair potential of the therapies by comparing MRI scans pre- and post-therapy.